2017
DOI: 10.1097/md.0000000000006923
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a mortality risk model for pediatric sepsis

Abstract: Pediatric sepsis is a burdensome public health problem. Assessing the mortality risk of pediatric sepsis patients, offering effective treatment guidance, and improving prognosis to reduce mortality rates, are crucial.We extracted data derived from electronic medical records of pediatric sepsis patients that were collected during the first 24 hours after admission to the pediatric intensive care unit (PICU) of the Hunan Children's hospital from January 2012 to June 2014. A total of 788 children were randomly di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…Therefore, although there was no statistical difference in the number of patients diagnosed with MODS between the two groups, these patients' prognoses differed. Mortality rate in the CASS group was predicted on mechanical ventilation, similar to those of several studies [35,36]. The need for invasive mechanical ventilation was considered as a risk factor for mortality due to the following reasons: (1) The patients treated with invasive ventilator had more severe condition: PIM2 at the ICU admission of CASS patients requiring mechanical ventilation was 11 (6.3, 25.9).…”
Section: Discussionsupporting
confidence: 70%
“…Therefore, although there was no statistical difference in the number of patients diagnosed with MODS between the two groups, these patients' prognoses differed. Mortality rate in the CASS group was predicted on mechanical ventilation, similar to those of several studies [35,36]. The need for invasive mechanical ventilation was considered as a risk factor for mortality due to the following reasons: (1) The patients treated with invasive ventilator had more severe condition: PIM2 at the ICU admission of CASS patients requiring mechanical ventilation was 11 (6.3, 25.9).…”
Section: Discussionsupporting
confidence: 70%
“…2, http://links.lww.com/CCM/G821 ). There were no mortality differences significantly associated with heart rate ( 47 , 53 , 58 , 71 , 74 , 76 ), mean blood pressure ( 53 , 71 ), systolic blood pressure ( 47 , 58 , 67 , 74 , 76 ), central venous pressures ( 51 , 53 , 71 ), and arterial oxygen saturations ( 47 , 58 ).…”
Section: Resultsmentioning
confidence: 87%
“…In adults, blood lactate greater than 2 mmol/L is now included within the operational definition of septic shock as an indication of cellular/metabolic dysfunction, and measurement of lactate is included in the Hour-1 Sepsis Bundle, with recommendations to repeat lactate measurement if the initial value exceeds 2 mmol/L [18,50,51]. In children, several observational studies have demonstrated an association of elevated blood lactate levels with adverse outcomes in septic shock [11,[52][53][54]. However, the optimal threshold to define "hyperlactatemia" remains unclear.…”
Section: Screening Diagnosis and Systematic Management Of Sepsismentioning
confidence: 99%
“…The optimal glucose target (between 140 and 180 mg/dL) necessitating control with insulin in children with septic shock or other sepsis-associated organ dysfunction (see Rec 47) Fever management in children with septic shock or other sepsis-associated organ dysfunction (see Rec 50) Hypocalcemia and supplements in children with septic shock or other sepsis-associated organ dysfunction (see Rec 48) Nutrition: three pathophysiology studies and seven RCTs Lipid solution effects on inflammatory physiology (see Rec 54) Early-vs late-enteral nutrition in children with septic shock or other sepsis-associated organ dysfunction (see Recs 51,52, and 53) The role of prokinetic agents in immunocompromised children with septic shock or other sepsis-associated organ dysfunction (see Rec 57) Bolus vs continuous enteral feeding in children with septic shock or other sepsisassociated organ dysfunction (see Rec 51,52,and 53) The prevalence of low serum vitamin C levels in children with septic shock or other sepsis-associated organ dysfunction (see Rec 62) Enteral nutrition vs parenteral supplementation of nutritional intake in the first 7 days of management of children with septic shock or other sepsis-associated organ dysfunction (see Rec 53) Dietary supplements (selenium, glutamine, arginine, zinc) in children with septic shock or other sepsis-associated organ dysfunction (see Recs 58,59,60,and 61) Vitamin C supplementation in children with septic shock or other sepsis-associated organ dysfunction (see Rec 62) Thiamine deficiency and supplementation in children with septic shock or other sepsisassociated organ dysfunction (see Rec 63) Vitamin D deficiency and supplementation in children with septic shock or other sepsisassociated organ dysfunction (see Rec 64) Blood products: two pathophysiology studies…”
Section: Knowledge Gaps and Research Opportunitiesmentioning
confidence: 99%